Pernyataan Yang Bertentangan Dengan Upaya Penegakan Hukum Pidana di Dalam Perspektif Kriminologi Hukum Yang Ada di Indonesia - Adwin Alvaro Jose Novalino; Margo Hadi Pura (Jurnal Ilmiah Wahana Pendidikan, 2022)
Statements that are generally contradictory to efforts to enforce criminal law in Indonesia in the perspective of legal criminology that often occur because of a conflict and conflicts that often occur are conflicts that occur between law enforcement officers in an effort to enforce criminal law in Indonesia. In addition, many law enforcement officials do not understand the contents of the legislation and the legal theories contained in it in depth, because the content contained in the legislation and the legal theories in it are basically just like a a knife used to carry out a legal analysis process that is considered sharp in an effort to enforce criminal law in Indonesia. Then the existence of contradictory and contradictory statements in efforts to enforce criminal law in Indonesia generally occurs because of the lack of knowledge of the legal apparatus itself in understanding the contents of legislation and legal theories so that in the process of enforcing criminal law it is often an error occurs, even though in existing and applicable legal theory, the law is the source of all legal sources used to resolve a criminal event that is ongoing and ongoing in the legal process among the community. The factors causing the emergence of contradictory statements and also the factors that invite the presence of contradictory statements in efforts to enforce criminal law in the perspective of legal criminology in Indonesia are factors from the law itself, factors from law enforcement officials themselves, factors from facilities, factors from the community environment as well as cultural factors. Efforts to enforce criminal law accompanied by contradictory statements in a criminological perspective can be carried out by revamping the system, with efforts to improve morals and values ​​contained and efforts to re-increase ethics for law enforcement officials, increase legal education and in an effort to increase knowledge in the field of religion